Kepemimpinan Kepala Madrasah dalam Inovasi Manajemen Pendidikan Di MTs N Diwek Jombang - Hajijah Hajijah; Ali Mustofa (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
The headmaster leadership is one of important factors to realize the vision, mission, goals, and objective of that school through the programs conducted planned and pushed. The headmaster eventually is required to have adequate management and leadership ability to be able to initiative in improving the school quality. The headmaster of Madrasah Tsanawiyah Negri Diwek Jombang has done education management function, such as planning, organizing, motivating, and controlling. The efforts have been done in educational management innovation of MTsN are: a) increasing the education personnel quality, b) improving the discipline of teachers, c) providing facilities and infrastructure. d) grouping students and e) creating program extracurricular and religious activities. The supporting factor is the teacher is active in assisting the implementation of innovation and the availability of infrastructure, while inhibiting factor is many teachers are not qualified.